THE HYBRIDITY IN CHIMAMANDA’S SHORT STORY NEWHUSBAND: A POSTCOLONIAL CRITICISM - Nabila, Qurrotun; Aminarti, Siska (Sekolah Tinggi Bahasa Asing JIA, 2025)
This study examines postcolonial hybridity in Chimamanda Ngozi Adichie’s short story The New Husband by focusing on everyday domestic practices through which identity is negotiated. According on Bhabha’s (1994) concept of hybridity, the research analyzes how language use, food practices, naming, and social etiquette reflect an in-between cultural position shaped by unequal power relations. Using a qualitative textual analysis based on close reading, the study finds that hybridity in the story is produced not through equal cultural exchange but through subtle forms of coercion within the domestic sphere, where patriarchal authority mirrors colonial domination. This research contributes to postcolonial hybridity studies by highlighting the home as a critical site of identity negotiation and by emphasizing women’s lived experiences of hybridity at the intimate, everyday level.